2021
DOI: 10.11648/j.abb.20210901.12
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Biological Attributes of <i>Momordica charantia</i>

Abstract: Momordica charantia is an herbal climber grown in tropical and subtropical regions, belonging to the Cucurbitaceae family. M. charantiacan be used as remedyagainst various diseases from ancient time. It has been used in various Asian traditional medicines for the treatment of cholera, bronchitis, anemia, blood diseases, ulcer, diarrhea, dysentery, gonorrhea rheumatism, gout, worms, colic, disease of liver and spleen, cancer and diabetes etc. The main constituents of M. charantia are triterpene, protein, steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Nanoparticles are used in packing of much food it avoid the anti microbial agents and saves the life [34]. The fascinating and vital properties of Ag nanoparticles amongst the other metallic nanoparticles like gold, tin, palladium etc have wide range of applications like anti bacterial, anti cancer, antiviral etc [35]. As, we know that nanoparticles are used in formation of nanomedicine.…”
Section: Role Of Nanoparticles In Disease Diagnosis and Treatmentmentioning
confidence: 99%
“…Nanoparticles are used in packing of much food it avoid the anti microbial agents and saves the life [34]. The fascinating and vital properties of Ag nanoparticles amongst the other metallic nanoparticles like gold, tin, palladium etc have wide range of applications like anti bacterial, anti cancer, antiviral etc [35]. As, we know that nanoparticles are used in formation of nanomedicine.…”
Section: Role Of Nanoparticles In Disease Diagnosis and Treatmentmentioning
confidence: 99%
“…presumed that "Considering the right now accessible medication medicines for IBS Peppermint oil might be the medication of first decision in IBS patients with non-genuine clogging or looseness of the bowels to mitigate general manifestations and to improve nature of life." In another 2007 preliminary, 75% of patients accepting peppermint oil saw a great half decrease of "all-out peevish entrails disorder score" [19,20]. Most as of late, an examination distributed January of this current year found that peppermint oil was viable in assuaging stomach torment in the runs prevalent bad tempered gut disorder [21,22].…”
Section: Effectiveness Of M Piperitamentioning
confidence: 99%
“…The pharmaceutical sector is crucial in providing society with goods and services that save lives. In managing the pandemic, the pharmaceutical sector faced a number of difficulties, including difficulty providing the demand for protective gear and diagnostic testing facilities [46]. • In order to find new, infectious infections, a system must be established for the creation, approval, and quick distribution of safe and efficient treatments to the entire world's population [30].…”
Section: The Effects Of Covid-19 On the Pharmaceutical Industrymentioning
confidence: 99%